RF way of impurity fluxes control in tokamaks - Grekov, D.L.; Kasilov, S.V. (Вопросы атомной науки и техники, 2000)
We have studied the influence of the local heating on the impurity flows in tokamaks in the Pfirsch-Schluter regime. If the effect of the thermoforce on the impurity ions is included into consideration, the impurity flux can be reversed by heating the impurities. This concept can be realized in tokamak experiments using RF heating. We describe the scheme of the RF heating of impurities and present estimates of the power required.